Ultrafast dynamics of 2-thiouracil investigated by time-resolved Auger spectroscopy. (17th December 2020) - Lever, F; Mayer, D; Picconi, D; Metje, J; Alisauskas, S; Calegari, F; Düsterer, S; Ehlert, C; Feifel, R; Niebuhr, M; Manschwetus, B; Kuhlmann, M; et al.
Abstract: We present time-resolved ultraviolet-pump x-ray probe Auger spectra of 2-thiouracil. An ultraviolet induced shift towards higher kinetic energies is observed in the sulfur 2p Auger decay. The difference Auger spectra of pumped and unpumped molecules exhibit ultrafast dynamics in the shift amplitude, in which three phases can be recognized. In the first 100 fs, a shift towards higher kinetic energies is observed, followed by a 400 fs shift back to lower kinetic energies and a 1 ps shift again to higher kinetic energies. We use a simple Coulomb-model, aided by quantum chemical calculations of potential energy states, to deduce a C–S bond expansion within the first 100 fs. The bond elongation triggers internal conversion from the photoexcited S2 to the S1 state. Based on timescales, the subsequent dynamics can be interpreted in terms of S1 nuclear relaxation and S1 -triplet internal conversion.